2021
DOI: 10.3389/fpsyg.2021.689534
|View full text |Cite
|
Sign up to set email alerts
|

Development of the N400 for Word Learning in the First 2 Years of Life: A Systematic Review

Abstract: The N400 ERP component is a direct neural index of word meaning. Studies show that the N400 component is already present in early infancy, albeit often delayed. Many researchers capitalize on this finding, using the N400 component to better understand how early language acquisition unfolds. However, variability in how researchers quantify the N400 makes it difficult to set clear predictions or build theory. Not much is known about how the N400 component develops in the first 2 years of life in terms of its lat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 126 publications
(205 reference statements)
2
14
0
Order By: Relevance
“…Developmental changes were indexed generally by a reduction of amplitude and latency in the N100 ( Albrecht et al, 2000 ; Pang and Taylor, 2000 ). Similarly, N400 was found reduced in adults, as well as other differences in latency and duration of the wave (for a recent systematic review, see Junge et al, 2021 ).…”
Section: Methodsmentioning
confidence: 93%
See 1 more Smart Citation
“…Developmental changes were indexed generally by a reduction of amplitude and latency in the N100 ( Albrecht et al, 2000 ; Pang and Taylor, 2000 ). Similarly, N400 was found reduced in adults, as well as other differences in latency and duration of the wave (for a recent systematic review, see Junge et al, 2021 ).…”
Section: Methodsmentioning
confidence: 93%
“…Based on the reviewed literature, we expected that if the processes underlying aSL with linguistic materials were early maturing and stable across development, as previous behavioral works suggest (e.g., Saffran et al, 1997;Raviv and Arnon, 2018;Shufaniya and Arnon, 2018), no differences should be observed in the electrophysiological correlates indexing SL in the brain, like the N100 and the N400 ERP components, even though slight differences might be observed due to differences in topography, amplitude, and latency arising from development and maturation factors (Albrecht et al, 2000;Pang and Taylor, 2000;Junge et al, 2021). In contrast, if aSL with linguistic materials elicited different neural responses in children and adults, as previous studies conducted either with adults or children suggest (e.g., Cunillera et al, 2006Cunillera et al, , 2009Abla et al, 2008;Bosseler et al, 2016;Mandikal-Vasuki et al, 2017a,b;Choi et al, 2020;Soares et al, 2020;Pierce et al, 2021), distinct modulations in the N100 and the N400 components should be observed.…”
Section: Current Studymentioning
confidence: 91%
“…Unlike adult studies, which focus on word prediction during sentence comprehension (as well as semantic priming), N400 investigations of language processing during early childhood have mostly been restricted to semantic priming paradigms or word‐picture matching tasks (Junge et al, 2021). Semantic priming refers to the facilitation of target processing (for example, of the word pear ) following the presentation of semantically related prime words (such as apple ).…”
Section: Introductionmentioning
confidence: 99%
“…In the real world, though, individual pictures rarely if ever flash on and off out of the darkness, and specific sequences of events virtually never reoccur. Similarly, in studies examining language acquisition, auditory evoked potentials tend to be measured relative to the presentation of individual nouns or sentences ( Junge et al, 2021 ), whereas real-world language comprehension critically requires parsing single words out of a complex, dynamic speech stream.…”
Section: Introduction – the Problem: Most Current Approaches To Study...mentioning
confidence: 99%